Duodenal occlusions: atresias, stenosis, and annular pancreas: Round Table Newborn intestinal occlusion; introduction and coordination Eduardo Anavitarte - Lattaro, Diver A (Cirugía del Uruguay, 1973)
he author reports newborn intestinal obstruction classification in general, and newborn duodenal obstruction classification, especially. The paper discusses newborn congenital duodenal obstruction by atresia, stenosis and annular pancreas (intrinsics duodenals causes). The annular pancreas is also considered as an intrinsic duodenal causeRickham-. He studies: its embriology ( types). its clinical, its phisionpathology, its radiology (characteristic double air pouch), its frequency, associated malformations, diagnosis and differencial diagnosis. Is described with emphasis, the vomiting contains bile, ( the point of obstruction below the papilla of Vater is the most frequent, in more than 90 % ), and the absence of abdominal distention is also appointed. By-pass operation is always made, and a side-to-side duodeno-jejunostomy isoperistaltic retrocolic, is considered in the treatment the surgical procedure of choice. Succesful depends of medically, surgically and nursery cares and an anesthesiologist with experience in newborn is required. Is pointed up, its high mortality. ,{50 - 60 % ) and a nor obstructive jaundice, by indirect bilirubin (MañéLattaro syndrome).